Periphytic diatom assemblages from Cip stream, Turkey: An examination of community relationships and habitat preferences - Yildirim, Vesile; Cetin, A. Kadri (My University, 2009)
Community structure of benthic diatoms in Cip stream was studied over a 1 -year period. A total of 72 taxa were identified from epipelic habitats as well as epilithic and epiphytic assemblages. The aim of this paper is to determine the species diversity and similarity of periphyton in different habitats of the stream. Of these, certain diatom taxa exhibited clear microhabitat preferences. Gomphonema acuminatum, Gomphonema parvulum, Placonesi elginensis and Rhopalodia musculus were recorded in the epilithic substrates. Epithemia argus and Pinnularia divergens were recorded only in the epipelic habitats, whereas Caloneis bacillum, Fragilaria ulna, Geissleria decussis, Nitzschia constricta and Pinnularia viridis were found only in the epiphytic assemblages.
Keywords: Diatoms; Periphyton; Streams; Substratum